ORGANOLEPTIC CHARACTERISTICS OF SAGO CRACKERS WITH THE ADDITION OF BIANG (Ilisha elongata) FISH FLOUR - Desti Maharani; Dahlia Dahlia; Sumarto Sumarto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
ABSTRACT            The biang fish can experience a decrease in quality so processing is needed to maintain its quality. One of processing is the manufacture of fortified fish  flour in the manufacture of sago crackers. The addition of biang fish flour in the manufacture of sago crackers can increase the nutritional value of sago crackers which are dominant with carbohydrates. The aim of this study was to analyze the effect of adding  biang fish flour to sago crackers. The experimental research method consisted of three stages, namely: 1) Making fish flour, 2) making sago crackers, and 3) organoleptic testing with using a non-factorial complete randomized design (CRD) with 4 levels; K0 (without fish flour), K1 (2.5% fish flour), K2 (5% fish flour), K3 (7.5% fish flour). The results showed that the appearance value were K0 (7.48%), K1 (6.91%), K2 (7.03%), and K3 (6.36%). The treatments K0, K1 and K2 were not significantly different, but the treatments K3 were significantly different. odor value were K0 (7.43%), K1 (7.85%), K2 (7.90%), and K3 (8.17%). The treatment of K0 was different from other treatments, but the treatment of K1, K2 and K3 was not significantly different. The taste value were K0 (7.08%), K1 (7.11%), K2 (7.85%), and K3 (8.15%). K0 and K1 treatments had no significant effect, but the K0 and K1 were significantly different from K2 and K3 treatments. The texture value were K0 (7.08%), K1 (7.56%), K2 (7.43%), and K3 (7.32%). Each treatment K0, K1, K2  and K3 significantly affected each other with all treatments.. The best treatment was 7.5% (K3) with the characteristics of crackers in the form of flat thickness, bright brown color, quite strong odor, delicious and savory taste, crunchy and dry texture. Keywords: Crackers, Diversification, Flour, Organoleptic.